Effects of COVID-19 on major blue-chip indices : a Nordic study - Ólöf Ragna Sigurðardóttir 1994- (2021)
The ongoing COVID-19 pandemic has made a negatively impacted the global financial markets. Studies on the impact have been conducted over the recent year in several countries using different methods. Few have covered the Nordics as well as looking at the second wave of the pandemic. The goal of this thesis is to assess the effect the pandemic has had on the Nordic stock markets. The Nordics consisting of Denmark, Finland, Iceland, Norway and Sweden. The assessment is made using daily COVID-19 cases as well as daily returns of the blue-chip stock market indices in each Nordic country. A TGARCH model is used in this thesis to determine whether an effect exists between COVID-19 and the Nordic stock markets. The results of the thesis are unable to confirm a significant effect COVID-19 has had on the Nordic stock markets with exception of Norway where the effect seemed to be positive. Keywords: COVID-19, TGARCH, GJR GARCH, Nordics, Major Blue-Chip Index, Stock Return.